Sektor Pertanian Unggulan di Sumatera Selatan - Oktavia, Zalika; Darwanto, Dwidjono Hadi; Hartono, Slamet (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Yogyakarta, 2015)
The objectives of this research were to analyze the contribution of agricultural sector to GRDP from South Sumatera, to identify agricultural leading sector and sub sector in South Sumatera, to analyze the growth component of agricultural sector. This research used GRDP time series data from year 2005-2013, with analytical methods used Location Quotient, Dynamic Location Quotient and Shift Share. The result of this research showed that agricultural sector contributed 21,79% on GRDP of South Sumatera, and the most contribute sub sector was plantation. The agricultural sector is still a leading sector. The agricultural sectors influenced positively of the national economics, but the growth is still lower than other sectors in South Sumatera, but nationally still compete with other provinces.